MULTIKULTURALISME DALAM BUKU AJAR AKIDAH AKHLAK DI MADRASAH ALIYAH PUTRI PUI MAJALENGKA - Yayat Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education plays a strategic role in shaping students’ tolerant and moderate attitudes within Indonesia’s multicultural society. The subject of Aqidah Akhlak has significant potential as a medium for internalizing multicultural values, as it is directly oriented toward the formation of students’ beliefs and behaviors in everyday life. Therefore, strengthening values such as tolerance, brotherhood, justice, and religious moderation is essential in Aqidah Akhlak learning in madrasah. This study aims to analyze the multicultural values contained in Aqidah Akhlak textbooks, examine the learning strategies used in their implementation, and identify the challenges encountered in Aqidah Akhlak learning at Madrasah Aliyah Putri PUI Majalengka. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews with Aqidah Akhlak teachers, participatory classroom observation, and documentation analysis of Aqidah Akhlak textbooks. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing.The findings indicate that multicultural values such as tolerance (tasāmuh), brotherhood (ukhuwah), social justice, and religious moderation (Islam wasathiyah) have been systematically integrated into both textbooks and learning practices. The implementation of these values is carried out through integrative and contextual learning strategies, including reflective discussions, socio-religious case studies, group work, role-playing, teacher exemplification, and habituation. Nevertheless, this study highlights a research gap, as existing studies on multicultural education have largely focused on general subjects and learning strategies, while in-depth analyses of multicultural value content in Aqidah Akhlak textbooks at the Madrasah Aliyah level remain limited.